Cursos frequentados por cotistas pretos, pardos e indígenas na UNIFESP - Freitas, Ísis Santana de (2024)
The starting point of this work is the Quotas Law 12.711/2012, and it questions whether the Law is truly an affirmative action or if it operates based on class prejudice, assuming it to be a State action because, despite quotas, the (governmental/state) absence persists, complicit in the exclusion of Black, Brown, and Indigenous individuals from social spaces. According to IBGE, as per the 2010 census, in the Municipality of São Paulo, the population was 11,253,503 inhabitants, with Black and Brown people comprising 37%, i.e., 4,164,504 residing in peripheral areas, occupying lower-paying jobs, and dedicating less time to their education. In terms of higher education, there is a significant disparity: 6.4% of the Black and Afro-descendant population gained access to higher education, while the White population had triple the access at 23.6%. This work aimed at investigating the effective actions and movements of the Federal University of the State of São Paulo (UNIFESP) aimed at the inclusion of quota students. Thus, the intention is to discuss – from an empirical and theoretical perspective – the admission of quota students into UNIFESP's undergraduate courses, with an emphasis on courses with higher and lower competition. The overall objective is to analyze – based on Law 12.711/2012 – the data collected by UNIFESP regarding the admission of Black, Brown, and Indigenous individuals in university courses. The dissertation was based on Florestan Fernandes' book (2007), in which the sociologist deconstructs the myth of racial democracy, and secondarily, the research will also draw on Frantz Fanon (2008), Clóvis Moura (2019), and Bourdieu (1975). Over the ten years of Law 12.711, it is concluded that Black, Brown, and Indigenous individuals mostly attend courses with lower demand. In this case, in the Interdisciplinary Science and Technology and Interdisciplinary Science and Technology of the Sea courses. Next is the Pedagogy course in the evening and afternoon terms. Thus, structural racism persists, maintaining the same White elite in the university seats of the most sought-after courses agreed upon in the pact of whiteness. Intellectualization of Black, Brown, and Indigenous individuals is necessary to regain human dimension, de-alienation, and decolonization for the anticolonial revolution in building new parameters of representation and social ascent because "where we are not seen, we do not think, we do not project"